Kepribadian Proaktif dan Perilaku Kerja Inovatif sebagai Prediktor Organizational Citizenship Behavior Mahasiswa Magang - Muhammad Iqbal Ar Rasyid; Pratista Arya Satwika (Universitas Kristen Maranatha, 2026)
This study investigates the role of proactive personality and innovative work behavior in predicting organizational citizenship behavior (OCB) among Generation Z interns. A quantitative method with purposive sampling was used, involving 214 Generation Z university students who had completed at least a three-month internship. Data were collected via online self-report questionnaires and analyzed using multiple linear regression. The results showed that proactive personality and innovative work behavior simultaneously played a significant role in predicting OCB, contributing to 25.6% of the variance. Partially, proactive personality had a significant positive effect on OCB, indicating that interns with proactive traits are more likely to engage in voluntary contributions. Conversely, innovative work behavior did not significantly predict OCB. The high cognitive demand required for realizing innovative ideas might lead to cognitive depletion, limiting interns' capacity to perform additional OCB during short-term internships. The study concludes that fostering a proactive personality is more effective than demanding innovation for enhancing OCB among temporary young talents.